Mujeres en la Colonia. Dominación colonial, diferencias étnicas y de género en cofradías y fiestas religiosas en Jujuy, Río de la Plata - Normando Cruz, Enrique (2005)
The article makes a comparative analysis of the participation of women in the fraternities and religious celebrations, and reveals that at the end of the colonial period there exists «distance between them» established by the economic, cultural and ethnical differences (Bourdieu 2000: 116), between the indigenous women of the rural world and the Spanish women of the elite and between the half-breed and Indian women of the urban shell. This study allows us to see that, while the voices of the female indigenous peasants of Purmamarca, Tumbaya or Cholacor enjoy themselves freely—and sometimes with the use of alcohol—in public spaces, where they work together with the men, and sing with periodical authority in the everyday life of the religious celebrations; the voices of the peasants of the cooperative and the indigenous women who make chicha in the San Salvador de Jujuy square are almost always dominated by a man, can pray their litany only in the chorus of the religious brotherhoods, in family life or in public work spaces which are authorized and controlled by men.